Creative Existential Therapy For Children, Adolescents and Adults (With Special Reference To Training (Existential Analysis: Journal of the Society for Existential Analysis, 2013)
This paper introduces several key features of the therapeutic approach Creative Existential Therapy for children, adolescents and adults. Firstly the creative space of the practice-workshop is introduced. Secondly the three parameters that are 'at play' in its conceptual framework are outlined. Finally the paper considers the three attitudes that are progressively introduced in the training of Creative Existential therapists.
Keywords: Being-in-creation; creative potentiality of being; creative relatedness; practice-workshop; symbolic sensed meaning; transpotentiality; trialogue